Otaria flavescens - Lucero, Sergio; Rodríguez, Sara M.; Teta, Pablo; Cassini, Guillermo; D'Elía, Guillermo (Zenodo, 2019)
Otaria flavescens (Shaw, 1800) Synonyms : aurita Bechstein, 1800; byronia de Blainville, 1820; chilensis Muller, 1841; chonotica Philippi, 1892; fulva Philippi, 1892; godeffroyi Peters, 1866; hookeri Schlater, 1866; leoninus F.G. Cuvier, 1827; minor Gray, 1874; molossina Lesson and Garnot, 1826; mollosinus Lesson, 1827; pernettyi Lesson, 1827; pygmaea Gray, 1874; rufa Philippi, 1892; ulloae Tschudi, 1844; uraniae Lesson, 1827; velutina Philippi, 1892. Neotype. MACN-Ma 23.26, Adult male, skull and mandible, almost without teeth, acquired by the Museo Argentino de Ciencias Naturales “Bernardino Rivadavia” on july 18th, 1923 (data on collector is missing) (Fig. 2). Type locality. San Sebastián (ca. -53.2979, -68.4512), Provincia de Tierra del Fuego, Antártida e Islas del Atlántico Sur, República Argentina (Fig. 3). Measurements of the neotype.- Condylobasal length = 346.4 mm; zygomatic width = 236.0 mm; braincase width = 120.5 mm; rostral length = 88.3 mm; rostral width = 100.0 mm; rostral height = 76.1 mm; postorbital constriction = 33.8 mm; mastoid width = 210.0; palatal length = 206.0 mm; palatal width = 55.0 mm; upper postcanine length = 94.0 mm; alveolus width of upper canine = 24.0 mm; length of dentary = 276.4 mm; coronoid height = 120.0; length of coronoid process = 89.0 mm; length of lower postcanine row = 81.0 mm; Distribution. Otaria flavescens is distributed along the Atlantic and Pacific coasts, from the Galápagos Islands in Ecuador (Pacific) and southern Brazil (Atlantic) in the north, to the archipelago of Tierra del Fuego and Islas Malvinas in the south (Aguayo and Maturana, 1973; Pine et al ., 1978; Sielfeld, 1983; Bastida et al ., 2007). Emended morphological diagnosis. (modified from Brunner, 2003) A species of the family Otariidae characterized by the following combination of character states: skull robust; rostrum sloped and broad, specially between the canines; nasals short and broad; preorbital processes well developed; interorbital constriction wide; supraorbital processes robust, ...